Aplikasi SMS Autoresponder untuk Otomatisasi Layanan Informasi Hasil Ujian Saringan Masuk di Universitas Wanita Internasional (Jurnal Teknologi dan Informasi, 2019)
Women International University is one of the developing universities and continues to improve services to stakeholders.  One form of service that needs to be improved is the new student admission information service (PMB), especially dissemination of the entrance results (USM).  In the current system the results of USM are informed through sending SMS (Short Message Services).  After completing USM, the PMB committee must prepare a message format and send SMS one by one to USM participants.  This way certainly requires a long time.  To overcome these problems, the solution offered is to build an SMS autoresponder application with aim to mkake the information service on USM results automated. Method used is object-oriented method and prototype system development method to build SMS autoresponder application.  Based on the results of tests conducted 10 times, the SMS autoresponder application can answer and send incoming filter test information, which is in the time span between 16-35 seconds with an average time of 22.22 seconds and the fastest time of 16.68 seconds.